Carbon taxes and compensation options - Maxime Bercholz; Barra Roantree (The Economic and Social Research Institute (ESRI), 2019)
This paper examines the effects an increase in the Irish carbon tax would have on households' incomes, and assesses potential options for compensating households. While a carbon tax rise would disproportionately affect lower-income households in isolation, we show that such households can be left financially better off on average by using the revenues raised to increase social welfare benefits and the state pension. We also show that a targeted increase in tax credits, maximum rates of welfare payments and Child Benefit can achieve the same distributional result as a lump-sum "cheque in the post", but with less administrative cost and complexity.
Keywords: 330